2019
DOI: 10.1177/0003489419834947
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Disparities in Patients Undergoing Endoscopic Sinus Surgery for Chronic Rhinosinusitis: Differences in Disease Presentation and Access to Care

Abstract: Objectives: Data on health care disparities by socioeconomic status for chronic rhinosinusitis (CRS) are lacking, and the available literature shows mixed results. The aim of this study was to evaluate several indicators of disease complexity in patients with CRS undergoing endoscopic sinus surgery between a private and a public hospital to determine if there are any disparities in the severity of disease presentation or in access to care. Methods: Two hundred patients with CRS who underwent endoscopic sinus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 33 publications
1
15
1
Order By: Relevance
“…Thirty-one articles were included in the final analysis after potentially overlapping studies were excluded. 1949 Figure 1 provides a summary of the search process. The risk of bias graph is presented as percentages across all included studies and summarized in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-one articles were included in the final analysis after potentially overlapping studies were excluded. 1949 Figure 1 provides a summary of the search process. The risk of bias graph is presented as percentages across all included studies and summarized in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…40 Duerson et al demonstrated that patients with CRS at a public hospital were more likely to be non-White, have nasal polyposis, and have CRS symptoms for 21% longer, likely secondary to decreased access to specialty care. 41 Previously published literature has also demonstrated racial disparities in rhinology treatment. When controlling for insurance and income status, Woodard et al found that Black and Hispanic individuals underwent ESS at significantly lower rates than White patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the potential interaction between nasal cavity breadth, NF orientation, and sinusitis remains unclear. Regardless, compared to the distinct MS morphology seen in our Asian sample, we would argue that these relatively minor differences in MS and NF morphology between individuals of European and African ancestry are less likely to contribute to health disparities between these populations compared to other known factors such as socioeconomic status, environmental stress, and access to healthcare (Duerson et al, 2019;Soler et al, 2012).…”
Section: Discussionmentioning
confidence: 70%